Occurrence and antimicrobial susceptibility profile of generic and Shiga toxin-producing Escherichia coli in raw beef from butcher shops in Addis Ababa and Burayu, Ethiopia - Negga Asamene Abera; Aklilu Feleke Haile; Eyasu Tigabu Seyoum; Tadesse Eguale (Discover Food)
Abstract Introduction Generic and Shigatoxin producing E. coli with higher rate of antimicrobial resistance traits are frequently recovered from food of animal origin such as beef. Multidrug resistant bacterial pathogens from foods have become critical public health significance. Therefore, this study aimed to assess occurrence and antimicrobial resistance profile of generic and Shigatoxin producing E. coli isolates from beef samples collected from selected butcher shops in Addis Ababa city and Burayu town, Ethiopia Methods. A cross-sectional study was conducted from August to December 2022. A total of 137 carcass (beef) swab samples were collected from 137 conveniently selected butcher shops. Specimens were inoculated into different agar plates, and colony morphology and biochemical characters were used for preliminary identification of E. coli. Confirmation and antimicrobial susceptibility testing were performed using an automated BD-Phoenix machine. Shiga toxin-producing E. coli were confirmed using multiplex polymerase chain reaction by amplifying target toxin, stx 1 , stx 2 , and eae attachment genes. Results. E. coli isolates were identified in 90 (81.0%) of samples analyzed. Twenty-two (19.8%) of the E. coli isolates were found to carry either Shigatoxin coding stx 1 and stx 2 (STEC) virulence genes, or eae attachment genes. The proportion of each gene among the positive isolates was 15 (68.2%) intimin, 3 (13.6%) stx1, and 4 (18.2%) stx2. A high rate of resistance was recorded to ampicillin 24 (21.6%) followed by cefoxitin 17(15.3%). Six (5.4%) and 5 (4.5%) of the isolates were positive for extended-spectrum β-lactamase, and carbapenemase production, respectively. In conclusion, a high proportion of beef samples were contaminated with Shigatoxin-producing E. coli, and MDR isolates to common classes of antimicrobials were detected among the E. coli beef isolates. Hence, there is a need for continuous monitoring to avoid the spread of MDR and food-borne pathogens to humans via food chains.